Fine‐needle aspiration of scalp masses: A review of 30 cases. Issue 2 (5th November 2022) - Doan, Mary; Ramani, Nisha S.; Arbab, Farinaz; Green, Linda K.
Abstract: Introduction: Scalp masses are often the initial presentation of a widely disseminated malignancy. Fine‐needle aspiration (FNA) is an optimal method for obtaining an accurate tissue diagnosis, in these patients with initial presentation and those with a known malignancy. Materials and Methods: We reviewed all FNAs of skin and soft tissue lesions from the scalp at our institution over a period of 31 years (1990–2021). Relevant clinical information was obtained from the review of computerized patient record. The histologic type, presentation, previous diagnoses, and survival after the diagnosis were correlated. Results: Thirty patients with scalp masses were identified. All the patients were males with a median age of 61 years (27–81 years). The scalp masses ranged from 0.4 to 6 cm in size. Ten cases (33%) were benign, but the majority of cases ( n = 20, 67%) were malignant. Of the malignant lesions sampled, 1 case was a primary squamous‐cell carcinoma (SCC), and the remaining 19 cases were metastatic tumors. Of these, 13 cases (68.4%) had a previously diagnosed malignancy. Most of the 19 metastatic lesions were adenocarcinomas or poorly differentiated carcinomas ( n = 12, 63.2%), followed by melanoma ( n = 4), SCC ( n = 1), alveolar soft part sarcoma ( n = 1) and large cell lymphoma ( n = 1). The most common site of primary was the gastrointestinal tract (6/19, 31.5%) and lung (6/19, 31.5%). The average survival after the diagnosis of these scalp metastases was around 6.3 months, signifying a poor prognosis. Conclusion: In our patient population, most scalp masses were metastatic tumors. Metastasis to the scalp signals advanced disease and is associated with a very poor prognosis. FNA is an easy, safe, rapid, cost effective and precise modality for diagnosing these masses. It can also yield material for molecular testing for newer directed therapies, if needed.